Arithmetic Garbling from Bilinear Maps - Fleischhacker, Nils; Malavolta, Giulio; Schröder, Dominique (Computer Security – ESORICS 2019, 2019)
We consider the problem of garbling arithmetic circuits and present a garbling scheme for inner-product predicates over exponentially large fields. Our construction stems from a generic transformation from predicate encryption which makes only blackbox calls to the underlying primitive. The resulting garbling scheme has practical efficiency and can be used as a garbling gadget to securely compute common arithmetic subroutines. We also show that inner-product predicates are complete by generically bootstrapping our construction to arithmetic garbling for polynomial-size circuits, albeit with a loss of concrete efficiency. In the process of instantiating our construction we propose two new predicate encryption schemes, which might be of independent interest. More specifically, we construct (i) the first pairing-free (weakly) attribute-hiding non-zero inner-product predicate encryption scheme, and (ii) a key-homomorphic encryption scheme for linear functions from bilinear maps. Both schemes feature constant-size keys and practical efficiency.
CRIS-Team Scopus Importer:2019-12-10